Māsu pieredze saskaroties ar pacienta nāvi Intensīvās terapijas nodaļā - Zālīte, Laima (Latvijas Universitāte, 2024)
Darba nozimīgumu nosaka tas, ka bieži vien māsu emocionālais stāvoklis saskaroties ar pacientu nāvi ir mazsvarīgs. Tamdēļ ir nepieciešams izpētīt māsu pieredzi, saskaroties ar pacientu nāvi. Iegūtās zināšanas palīdzēs izstrādāt nepieciešamās rekomendācijas un ieteikumus Intensīvās terapijas māsām saskaroties ar pacientu zaudējumu. Tāpat, apkopojot iegūto informāciju, mēs varam izzināt par katras māsas individuālo pieredzi, saskaroties ar pacientu nāvi, un tās ietekmi uz emocionālo stāvokli. Pētījuma jautājums: kāda ir intensīvās terapijas nodaļas māsu pieredze saskaroties ar pacienta nāvi? Pētījuma mērķis: noskaidrot intensīvās terapijas nodaļas māsu pieredzi pacienta nāves gadījumā un izstrādāt ieteikumus. Bakalaura darba apjoms sastāv no 36 lapaspusēm. Darbā tika izmantoti 30 literatūras avoti. Darbs sastāv no 6 nodaļām un 2 apakšnodaļām, secinājumiem un , izmantotās literatūras sarakstu un pielikumiem

Nurses often face a significant emotional and ethical burden when caring for dying patients. Addressing these struggles requires a combination of adequate training in palliative care, support from a multidisciplinary team, clear communication, and access to mental health resources to help nurses cope with the emotional demands of end-of-life care. To explore the research questions about nurses' experiences with patient loss in the Intensive Care Unit (ICU) and how they recover from it, I’m breaking down these questions into a set of more detailed sub-questions that will help guide data collection and analysis. Summarizing the information gathered from My research, this could provide valuable insights into the personal and emotional experiences of nurses when dealing with patient loss in the ICU. By evaluating individual cases or specific situations, I can offer a detailed, nuanced perspective on how these experiences affect nurses' emotional states and coping mechanisms. Research question: What is the experience of nurses in the intensive care unit in case of patient loss? The aim of the research: to find out the experience of the nurses of the c intensive care unit in case of patient loss and to develop proposals. The volume of the bachelor's thesis consists of 36 pages. 30 sources were used in the work. The work consists of 6 chapters and 2 subsections, references and appendices. Keywords: death, patient, loss, nurses, experience, intensive care.
Nurses' experience of dealing with patient death in the intensive care unit
Keywords: Veselības un sporta zinātnes; Pieredze; Nāve; ITN; Pacients; Māsa